Peran Serta Masyarakat dalam Pengelolaan Wilayah Pesisir di Kota Kendari - Jabalnur . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT The objective of this writing is to know thepublic participation in decentralizing of coastal zone management. This type of research is normative research by using secondary data that data is not obtained directly rom the field, but by studying the literature of research results and other sources that relevantto theinvestigated issues. The data was collected then analyzed by descriptive qualitative. The conclusion is that public participation in decentralizing of coastal zone management that the public was given the authority, responsibility, and opportunity to manage its resources and also involved giving responsibility to the community so that they could make decisions that ultimately determined and affected their welfare. Community involvement in the management strategies tailored to each area would vary according to local circumstances. In implementation of public participation, the things to be noted are the values and norms that embraced by a society which is the local wisdom in managing natural resources and environment. Key word: public, management, coastal zone